Distribuiç\~ao funcional da renda no Brasil: Estimativas anuais e construç\~ao de uma série trimestral - Estêv\~ao Kopschitz Xavier Bastos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– In this paper, we present a calculation of a quarterly series of the labor share in the Brazilian GDP, and an annual estimate based on PNAD (National Household Survey) and the quarterly GDP, for the years in which annual national accounts are not yet available. The theme of the functional distribution of income is addressed through a brief literature review. The functional distribution for Brazil is calculated following Gollin (2002) adjustments. Fluctuations in labor and capital shares are observed in Brazil from 1970 to 2009, but the question is whether these fluctuations are significant or not, from the point of view of rejection of the hypothesis of the Cobb-Douglas function, which implies this shares should be constant. It is observed that changes in functional income distribution both in the direction favorable to labor and in the direction favorable to capital are consistent with a reduction in personal income distribution inequality. Based on the literature review, variables that can affect the functional distribution of income are listed.
Keywords: E10; O54; 330; Funktionelle Einkommensverteilung; Brasilien